DEFINITION OF OPERATING PARAMETERS OUTPUT RANGE OF FUNCTIONAL SUBSYSTEMS HYDRAULIC SYSTEMS OF THE AIRCRAFT - M. A. Bobrin; L. G. Klemina; A. N. Kozlov (Научный вестник МГТУ ГА, 2016)
To evaluate the operational tolerance field hydraulic output parameters under various working conditions and the flight stages are mathematical relationships and the results obtained in the environment Mathcad in graphical form.